ICHKI ZIDDIYATLAR VA AXLOQIY TANLOV: DOSTOYEVSKIY ADABIYOTINING RUHIY MANZARALARI - Qayumova Dilobar,; Ochilova Muxlisabonu, (TADQIQOTLAR, 2025)
Annotation:  This  article  offers  a  comprehensive  exploration  of  the  central themes in Fyodor Dostoevsky’s literary works, emphasizing his profound engagement with psychology, morality, faith, and society. It examines Dostoevsky’s deep dive into the human psyche, focusing on inner conflict, guilt, and the moral tension between good and evil. Core themes such as suffering as a path to redemption, the burden of free will, and the existential struggle between belief and atheism are analyzed through key works like Crime and Punishment, The Brothers Karamazov, and Notes from Underground.